Risk Factors for Stunted Growth among Children Aged 6–59 Months in Rural Uganda - John, Bukusuba; Archileo, N. Kaaya; Abel, Atukwase (International Journal of Nutrition, 2017)
Despite the agreed global and national stunting reduction targets, Uganda has made very little progress. Understanding context-specific risk factors for stunted growth is therefore pertinent to designing programs to address the problem. A cross-sectional study was conducted in 32 randomly selected villages in Buhweju district, Southwest Uganda. Data entry, cleaning and analysis were carried out using Statistical Package for Social Sciences (SPSS) version 21. A regression analysis was conducted to examine the associations between potential risk factors and stunted growth. The survey covered 256 households and anthropometric measurements were taken for 221 children aged 6–59 months. The majority of the households (66%) in the district were food insecure and had a low socioeconomic status (84%). The prevalence of stunting in Buhweju district was 51%, which is significantly higher than the regional and national averages. Only 28% of the children were exclusively breastfed in the first 6 months of life, and only 10% of them received the minimum acceptable diet (MAD). The findings of this study demonstrate that reductions in stunted growth at national or regional levels has not necessarily translated into similar trends in rural areas of Uganda. The notable contributors to stunting in these areas include morbidity, sub-optimal infant and young child feeding (IYCF) practices, low consumption of animal-source foods, food insecurity, lack of access to high-quality drinking water, sanitation and hygiene (WASH) facilities and poverty. Increased investment in both nutrition specific and sensitive interventions is therefore crucial to address these risk factors.
Keywords: Stunting; Food security; Socioeconomic status; IYCF